Towards Equal Status: English-Speaking Minority Communities in Canada and the Official Languages Act - Martin-Laforge, Sylvia (Minorités linguistiques et société / Linguistic Minorities and Society)

(untitled) (Institut canadien de recherche sur les minorités linguistiques / Canadian Institute for Research on Linguistic Minorities, 2021)
The introduction of the Report of the Royal Commission on Bilingualism and Biculturalism lays the foundation for two official language minority communities in Canada, and the principle of equality, which “implies respect for the idea of minority status, both in the country as a whole and in each of its regions.” However, the Official Languages Act that flowed from the ‘Bi and Bi Commission, and the structures that oversee it, have not reflected an approach based on equality. The English-speaking community of Quebec—Canada’s English linguistic minority community—has not received “generous treatment” in the implementation of the Act. This paper based on my presentation at the 87th annual Acfas congress, offers some ideas about why this situation has developed and the impact this has had on the vitality of Quebec’s English-speaking community. I conclude that equality for both official language minority communities—the outcome envisioned by the Commissioners—must be achieved through the modernization of the Official Languages Act.